Measuring empathy in pediatrics: validation of the Visual CARE measure - Michele Arigliani; Luigi Castriotta; Anna Pusiol; Annachiara Titolo; Enrico Petoello; Alberto Brun Peressut; Elisabetta Miorin; Iana Elkina; Federico Marzona; Davide Cucchiaro; Elisa Spanghero; Matteo Pavan; et al. (BMC, 2018)
Abstract Background Empathy is a key element of "Patient and Family Centered Care", a clinical approach recommended by the American Academy of Pediatrics. However, there is a lack of validated tools to evaluate paediatrician empathy. This study aimed to validate the Visual CARE Measure, a patient rated questionnaire measuring physician empathy, in the setting of a Pediatric Emergency Department (ED). Methods The empathy of physicians working in the Pediatric ED of the University Hospital of Udine, Italy, was assessed using an Italian translation of the Visual Care Measure. This test has three versions suited to different age groups: the 5Q questionnaire was administered to children aged 7-11, the 10Q version to those older than 11, and the 10Q-Parent questionnaire to parents of children younger than 7. The internal reliability, homogeneity and construct validity of the 5Q and 10Q/10Q-Parent versions of the Visual Care Measure, were separately assessed. The influence of family background on the rating of physician empathy and satisfaction with the clinical encounter was also evaluated. Results Seven physicians and 416 children and their parents were included in the study. Internal consistency measured by Cronbach's alpha was 0.95 for the 10Q/10Q-Parent versions and 0.88 for the 5Q version. The item-total correlation was > 0.75 for each item. An exploratory factor analysis showed that all the items load onto the first factor. Physicians' empathy scores correlated with patients' satisfaction for both the 10Q and 10Q-Parent questionnaires (Spearman's rho = 0.7189; p < 0.001) and for the 5Q questionnaire (Spearman's rho = 0.5968; p < 0,001). Trust in the consulting physician was lower among immigrant parents (OR 0.43. 95% CI 0.20-0.93). Conclusions The Visual Care Measure is a reliable second-person test of physician empathy in the setting of a Pediatric Emergency Room. More studies are needed to evaluate the reliability of this instrument in other pediatric settings distinct from the Emergency Room and to further evaluate its utility in measuring the impact of communication and empathy training programmes for healthcare professionals working in pediatrics.